Molecular combined carbohydrate composition and concentrations in four trophic regimes of the Southwestern Pacific Ocean - Barthelmeß, Theresa; Engel, Anja (In: Barthelmeß, Theresa; Cristi, Antonia; Deppeler, Stacy; Safi, Karl; Sellegri, Karine; Law, Cliff S; Engel, Anja (2025): Diel dissolved organic matter cycling and phytoplankton abundance in four trophic regimes of the South Pacific Ocean [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.974276, 2025)
Samples were collected in the surface of the Southwestern Pacific Ocean in subtropical and sub-Antarctic water masses, above the Chatham Rise and at the entrance of the Cook Strait in well mixed water masses, creating distinct oligotrophic and eutrophic regimes, respectively. Diel dynamics in concentrations of the molecular components of dissolved combined carbohydrates (D_CCHO) and total combined carbohydrates (T_CCHO) are presented.
Keywords: amino acids; carbohydrates; chlorophyll-a; Dissolved Organic Matter; flow cytometry; surface water